COMPARING PROPOFOL AND FENTANYL-MIDAZOLAM COMBINATION FOR CONSCIOUS SEDATION IN FIBREOPTIC NASOTRACHEAL INTUBATION: A PROSPECTIVE STUDY - Shrikanta; Gaur, Divyansh; Jayantilal, Shah Raj; Raza, Ali; Gupta, Sachin Kumar (Student’s Journal of Health Research Africa, 2024)
Background Awake fibreoptic intubation is crucial for managing difficult airways. The efficacy of propofol compared to a fentanyl-midazolam combination for conscious sedation during this procedure has not been extensively documented. The purpose of this study is to compare the effectiveness of propofol with the commonly used fentanyl and midazolam combination for conscious sedation during nasotracheal FOI. Methods This prospective study was conducted over six months at Deen Dayal Upadhyay Hospital, involving 60 patients divided into two groups. One group received propofol, while the other was administered a fentanyl-midazolam combination. The outcomes measured included the quality of sedation, intubating conditions, hemodynamic changes, degree of amnesia, and global acceptance. Results Propofol significantly outperformed the fentanyl-midazolam combination in terms of sedation quality (8.2 vs. 6.7), intubating conditions (85% vs. 70% rated as excellent), and amnesia (90% vs. 60% with no recall). Global acceptance was also higher in the propofol group (9.0 vs. 7.5). Both groups maintained stable hemodynamics throughout the procedures. Conclusion Propofol offers superior sedation quality, improved intubating conditions, more profound amnesia, and higher overall acceptance compared to the fentanyl-midazolam combination for conscious sedation in fibreoptic nasotracheal intubation. These attributes suggest propofol is a preferable choice in clinical practice for managing difficult airways. Recommendation The benefits to using propofol makes it a better option in clinical practice for managing challenging airways, include improved sedative quality, ideal intubating circumstances, steady hemodynamic responses, profound amnesia, and increased worldwide acceptability.